Universal Health Coverage for Inclusive and Sustainable Development: Lessons from Japan - Ikegami, Naoki (World Bank, 2015)
The goals of universal health coverage (UHC) are to ensure that all people can access quality health services, to safeguard all people from public health risks, and to protect all people from impoverishment due to illness, whether from out-of-pocket payments for health care or loss of income when a household member falls sick. Countries as diverse as Brazil, France, Japan, Thailand, and Turkey have shown how UHC can serve as a vital mechanism for improving the health and welfare of their citizens and lay the foundation for economic growth and competitiveness grounded in the principles of equity and sustainability. Ensuring universal access to affordable, quality health services will be an important contribution to ending extreme poverty by 2030 and boosting shared prosperity in low-income and middle-income countries, where most of the world?s poor live.